COORDINATION ABILITIES IN YOUNG SWIMMERS AS THE IMPORTANT FACTOR OF FUTURE SUCCESS IN WORLD CHAMPIONSHIPS (Лучшие интеллектуальные исследования, 2025)
Abstract: Coordination abilities in swimming—specifically the timing and interaction of arm strokes—may be a decisive factor in determining which young athletes eventually excel at the elite level. This theoretical paper proposes that early development of advanced stroke coordination patterns (such as overlapping arm propulsion with minimal glide) strongly correlates with greater success in later international competitions. We review current research on front crawl coordination and performance, develop a framework linking early coordination skills to long-term competitive outcomes, and discuss supportive findings. Key studies show that as swimmers increase speed, they transition from a catch-up style stroke to a superposition (overlap) mode, and that elite swimmers maintain more stable intracyclic velocity than novices. We further incorporate new data visualizations of training interventions that improved young swimmers’ stroke length and inter-limb coordination. These insights collectively suggest that coaching practices focusing on coordination development in youth could enhance the likelihood of future championship success.